Gambaran karakter diri pelaku seni tari prajuritan di desa Banyubiru - Emmanuel Satyo Yuwono; Doddy Hendro Wibowo (Universitas Sarjanawiyata Tamansiswa, 2023)
Prajuritan is a war dance where a group of men and women dance together. Warrior dance, full of meaning, is a form of local wisdom that the people in Banyubiru Village, Semarang Regency, Central Java Province live. This research aimed to discover the self-characteristic description of Tari Prajuritan performers in Banyubiru Village. This study implemented a phenomenological-descriptive qualitative method. The data were collected through interviews and observation. The participants in this study were 3 Tari Prajuritan dancers from Banyubiru Village. The research results on the self-characteristic description of Tari Prajuritan dancers include firmness in decision-making, a confident character in relationships, responsibility, and an attitude toward serving others.